Review on Panton Valentine Leukocidin Toxin Carriage among Staphylococcus aureus - Shrestha, B (Journal of Nepal Health Research Council, 2014)
Panton Valentine leukocidin is a toxin making pores in the polymorphonuclear cells whichis a virulence factor of some strains of Staphylococcus aureus. Initially it was produced by methicillin susceptible Staphylococcus aureusonly. Later with the acquisition of mecAgene has lead it to be PVL positive methicillin resistant Staphylococcus aureus. Since MRSA are resistant to many antibiotics and further they produce a toxin the infections by PVL positive MRSA has become a challenge. PVL positive MRSA a virulent strain of drug resistant superbug MRSA that has spread around the world, has claimed many lives in UK, Europe, USA and Australia. Some strains of superbug attack the healthy young people and kill within 24 hrs.PVL positive Staphylococcus aureushas been reported to be associated with skin and soft tissue infections however they also cause invasive infections and necrotizing pneumonia. These microorganisms known to be community associated have spread to hospitals. Hospital acquired infection by such microorganisms lead to an increase in mortality hence should be controlled before they become prevalent in hospitals. Keywords: community acquired; hospital acquired ;MRSA;MSSA; PVL.